Ball-flower-shaped magnesium silicate anthraquinone degradation product regeneration catalyst as well as preparation method and application thereof

The preparation of the flower spherical magnesium silicate anthraquinone degradate regeneration catalyst through self-template and growth induction methods has solved the problem of poor regeneration performance of anthraquinone degradate in the prior art, and achieved the effects of high catalytic activity, long service life and low production cost.

CN119660755AActive Publication Date: 2025-03-21BEIJING UNIV OF CHEM TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411947949.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-21
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The prior art has problems of poor regeneration performance, short service life and high production costs when treating anthraquinone degradable substances, resulting in a decrease in the catalytic efficiency of palladium-based catalysts and an increase in product costs.

Method used

Porous magnesium silicate microspheres were prepared by self-template and growth-induced methods, and a floral spherical magnesium silicate anthraquinone degradation catalyst was obtained through alkali activation, which had better anthraquinone reactive properties and long service life.

Benefits of technology

A catalyst with high catalytic activity, good selectivity and long service life was achieved. The regeneration capacity of anthraquinone degraded substances reached 9.33 g/L within 72 hours, and the regeneration capacity could still reach 8.87 g/L after 6 months of use, reducing production costs and improving product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660755A_ABST
    Figure CN119660755A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a flower-ball-shaped magnesium silicate anthraquinone degradation product regeneration catalyst, which comprises the following steps: adding ammonia water into an aqueous solution of magnesium salt, and standing for reaction to obtain magnesium hydroxide slurry; ammonium salt and a growth inducer are added into the magnesium hydroxide slurry, stirring reaction is performed, then the silicate solution is dropwise added into the magnesium hydroxide slurry, and ultrasonic treatment is performed after dropwise adding is completed; transferring the slurry subjected to ultrasonic treatment into a hydrothermal reaction kettle, carrying out microwave heating reaction, cooling to room temperature after the reaction is completed, carrying out centrifugal washing with deionized water, and drying the obtained filter cake to obtain magnesium silicate powder; adding magnesium silicate powder into a sodium hydroxide solution, stirring for reaction, and washing and drying after the reaction is finished to obtain the ball-flower-shaped magnesium silicate anthraquinone degradation product regeneration catalyst. The prepared flower-ball-shaped magnesium silicate anthraquinone degradation product regeneration catalyst is green, environment-friendly, non-toxic and harmless, and has the advantages of high catalytic activity, good selectivity, long service life and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of catalyst technology, and more specifically, to a spherical magnesium silicate anthraquinone degradation product regeneration catalyst and a preparation method and application thereof. Background Art

[0002] In the process of producing H2O2 by the anthraquinone method, due to the complexity of organic reactions, even if the most selective catalyst is used, some anthraquinone substances that lose the ability to produce H2O2 will still be produced. These substances are collectively referred to as anthraquinone degradation products. With the continuous circulation of the working solution, the degradation products in the anthraquinone working solution will gradually accumulate. Excessive levels of anthraquinone degradation products will affect operations such as hydrogenation, oxidation and extraction to varying degrees, and cause an increase in the organic carbon content in the product, seriously affecting the yield and quality of the H2O2 product, thereby affecting the catalytic efficiency of the palladium-based catalyst. In addition, excessive levels of anthraquinone degradation products will also increase the viscosity and density of the working solution, increase the resistance of the pipeline transportation device, and thus increase the product cost. Therefore, it is necessary to regenerate the anthraquinone degradation products to restore their production capacity.

[0003] At present, the commonly used treatment method is to use a solid base catalyst, but because its alkaline components are easy to lose, there are problems such as poor regeneration performance and short service life. In actual production, in order to ensure the stability of product output, it is necessary to frequently replace the regenerated catalyst, resulting in loss of working fluid and the generation of a large amount of waste catalyst solid waste. Magnesium silicate has the characteristics of rich surface hydroxyl groups, large specific surface area, low solubility, etc., and has broad application prospects in the fields of adsorption and catalysis, which has attracted close attention from researchers. For example, patent CN117602636A discloses a preparation method of anthraquinone regeneration catalyst of attapulgite magnesium silicate, anthraquinone regeneration catalyst and its application. It uses attapulgite and magnesium chloride as silicon sources and magnesium sources, uses a hydrothermal method, and hydrothermally heats at 140°C for 12h to prepare attapulgite magnesium silicate, which is used for the regeneration of anthraquinone degradation products. However, the magnesium silicate prepared by the patent has a small pore size, which is not conducive to the diffusion of reactants and products, the utilization rate of active sites is low, and the catalytic activity is not ideal. Moreover, the preparation process is relatively complicated. The hard template method requires the use of attapulgite and a two-step reaction. The reaction cycle is too long and the yield is low, which is not conducive to industrial production. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention adopts the self-template and growth induction method to prepare porous magnesium silicate microspheres, and obtains flower-shaped magnesium silicate anthraquinone degradation product regeneration catalyst after alkali activation. The specific surface area of ​​the porous magnesium silicate microspheres synthesized in the present invention is 550-650m 2 ·g -1 , pore volume 0.80-1.0cm 3 ·g -1The average pore size is 6-7nm, and it has good anthraquinone regeneration activity. The flower ball-shaped magnesium silicate anthraquinone degradation product regeneration catalyst prepared in the present application does not need to use other templates, has a short reaction time, is green and environmentally friendly, non-toxic and harmless, and has the advantages of high catalytic activity, good selectivity, and long service life.

[0005] In order to achieve the above objectives, in a first aspect, the present application provides a method for preparing a regeneration catalyst of anthraquinone degradation product of spherical magnesium silicate, comprising the following steps:

[0006] Step 1: adding ammonia water to an aqueous solution of magnesium salt, and allowing to stand for reaction to obtain magnesium hydroxide slurry;

[0007] Step 2: adding the ammonium salt and the growth inducer to the magnesium hydroxide slurry, stirring for reaction, then dropping the silicate solution into the magnesium hydroxide slurry, and performing ultrasonic treatment after the dropping is completed;

[0008] Step 3: transferring the slurry after ultrasonic treatment to a hydrothermal reactor, heating with microwaves for reaction, cooling to room temperature after the reaction is complete, washing with deionized water by centrifugation, and drying the obtained filter cake to obtain magnesium silicate powder;

[0009] Step 4: adding magnesium silicate powder to sodium hydroxide solution, stirring for reaction, washing and drying after the reaction is completed, and obtaining a spherical magnesium silicate anthraquinone degradation product regeneration catalyst.

[0010] Furthermore, the standing time in step 1 is 0.5-3h.

[0011] Furthermore, in step 1, the magnesium salt is any one or more combinations of magnesium chloride, magnesium nitrate or magnesium sulfate.

[0012] Furthermore, in step 1, the concentration of the aqueous solution of the magnesium salt is 0.2-0.5 mol / L, the concentration of the ammonia water is 6-8 mol / L, and the molar ratio of Mg in the magnesium salt to the ammonia water is 1-2:1.

[0013] Furthermore, the ammonium salt described in step 2 is any one or more combinations of ammonium chloride, ammonium nitrate or ammonium sulfate.

[0014] Furthermore, the silicate described in step 2 is sodium silicate or potassium silicate.

[0015] Furthermore, the growth inducer described in step 2 is any one or more combinations of dodecyl ethoxy sulfobetaine, sodium lauryl polyether sulfate, and lauryl glucoside.

[0016] Furthermore, in step 2, the ultrasonic time is 10-30 min.

[0017] Furthermore, the stirring reaction time in step 2 is 1-4h.

[0018] Furthermore, in step 2, the concentration of the silicate is 0.2-0.5 mol / L, the molar ratio of Si to Mg is 1-1.5:1, the molar ratio of ammonium salt to Mg is 1:2-1, and the molar ratio of growth inducer to Mg is 0.05-0.5:1.

[0019] Furthermore, the microwave heating reaction procedure in step 3 is to react at 120-150° C. for 2-4 h, then increase the temperature to 180-240° C. and continue the reaction for 6-12 h.

[0020] Furthermore, the drying condition in step 3 is drying at 100-150° C. for 12-24 hours.

[0021] Furthermore, in step 4, the concentration of the sodium hydroxide solution is 5-10 mol / L; the stirring reaction temperature is 80-150° C., and the time is 2-4 h.

[0022] In a second aspect, the present invention provides a flower spherical magnesium silicate anthraquinone degradation product regeneration catalyst, which is prepared by the above-mentioned preparation method, and the chemical formula of the flower spherical magnesium silicate anthraquinone degradation product regeneration catalyst is Mg4Si6O 15 (OH)2·6H2O.

[0023] In a third aspect, the present invention provides the application of the above-mentioned flower spherical magnesium silicate anthraquinone degradation product regeneration catalyst or the preparation method of the flower spherical magnesium silicate anthraquinone degradation product regeneration catalyst in the regeneration of anthraquinone degradation products.

[0024] The technical solution provided by this application has at least the following beneficial effects compared with the prior art:

[0025] 1) The present invention provides a method for preparing a regeneration catalyst for anthraquinone degradation products of spherical magnesium silicate, which has the advantages of wide raw material sources, simple preparation process, green environmental protection, low production cost, and convenience for industrial production.

[0026] 2) The flower-spherical magnesium silicate anthraquinone degradation product regeneration catalyst prepared by the present invention is green, environmentally friendly, non-toxic and harmless, has the advantages of high catalytic activity, good selectivity, long service life, etc., and the regeneration capacity of anthraquinone degradation products can reach 9.33g / L within 72h. The regeneration capacity can still reach 8.87g / L after 6 months of use. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The X-ray diffraction spectrum of the regeneration catalyst of the spherical magnesium silicate anthraquinone degradation product prepared in Example 1;

[0028] Figure 2 This is a scanning electron microscope image of the regeneration catalyst of the spherical magnesium silicate anthraquinone degradation product prepared in Example 1;

[0029] Figure 3 This is a graph showing the regeneration performance of the spherical magnesium silicate anthraquinone degradation product regeneration catalyst prepared in Example 1. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to understand the present application more clearly, the present application is further described in detail below in conjunction with examples and drawings. However, it should be understood that the following examples are only preferred implementation methods of the present application, and the scope of protection required by the present application shall be based on the scope defined in the claims.

[0031] In the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0032] <Example>

[0033] Example 1

[0034] A spherical magnesium silicate anthraquinone degradation product regeneration catalyst is prepared by the following method:

[0035] Step 1: weigh 10.03 g (0.0400 mol) of magnesium nitrate and dissolve it in 200 mL of deionized water to obtain a magnesium nitrate solution, add 3 mL (8 mol / L) of ammonia water to the magnesium nitrate solution, and let it stand for 1 hour to react to obtain a magnesium hydroxide slurry;

[0036] Step 2: Add 1.00 g (0.0211 mol) of ammonium chloride and 1.50 g (0.00520 mol) of lauryl glucoside to the magnesium hydroxide slurry, and stir to react for 2 h; dissolve 15.06 g (0.0521 mol) of sodium silicate in 150 mL of deionized water to obtain a sodium silicate solution, and use a circulation pump to add the sodium silicate solution drop by drop to the magnesium hydroxide slurry, and stir and ultrasonically disperse for 20 min;

[0037] Step 3: The slurry after ultrasonic treatment was transferred to a hydrothermal reactor, heated to 130 degrees by microwave, reacted for 3 hours, then heated to 200 degrees, continued to react for 8 hours, naturally cooled to room temperature, centrifuged and washed 4 times with deionized water, and the obtained filter cake was dried in an oven at 120 degrees for 24 hours, and ground through a 100 mesh sieve to obtain magnesium silicate powder;

[0038] Step 4: Take 5.00g (0.05mol) of magnesium silicate powder and add it to 100mL (5mol / L) of sodium hydroxide solution, stir and react at 130°C for 3h, cool to room temperature, centrifuge and wash four times with deionized water, dry the obtained filter cake in an oven at 60°C for 12h, and grind it through a 100-mesh sieve.

[0039] Characterization and testing:

[0040] 1. The flower-shaped magnesium silicate anthraquinone degradation product regeneration catalyst obtained in Example 1 was subjected to XRD analysis, and the obtained XRD diffraction spectrum was as follows: Figure 1 As shown. Figure 1 It can be seen that its XRD diffraction peak is similar to that of Mg4Si6O 15 The standard card of (OH)2·6H2O (JCPDS:29-1492) corresponds to that of (OH)2·6H2O.

[0041] 2. The morphology of the flower-shaped magnesium silicate anthraquinone degradation product regeneration catalyst prepared in Example 1 was characterized by scanning electron microscopy. Figure 2 As shown. Figure 2 It can be seen that the catalyst has a multi-level flower ball structure assembled by nanosheets.

[0042] 3. The regeneration catalytic performance of the flower-shaped magnesium silicate anthraquinone degradation product regeneration catalyst prepared in Example 1 was tested. The test steps were as follows: 5.00 g of flower-shaped magnesium silicate anthraquinone degradation product regeneration catalyst was added to 50 mL of working solution. After 72 hours, 50 uL of anthraquinone regeneration solution was taken and placed in a 10 mL volumetric flask and fixed to volume with anhydrous methanol. The anthraquinone regeneration amount was tested on a liquid chromatograph. The test results are as follows: Figure 3 As shown. Figure 3 It can be seen that the flower-spherical magnesium silicate anthraquinone degradation product regeneration catalyst prepared in Example 1 has a high regeneration performance for anthraquinone degradation products, and the regeneration capacity reaches 9.33 g / L within 72 hours. After 6 months of use, the regeneration capacity can still reach 8.87 g / L.

[0043] Example 2

[0044] A spherical magnesium silicate anthraquinone degradation product regeneration catalyst is prepared by the following method:

[0045] Step 1: Weigh 12.06 g (0.0480 mol) of magnesium nitrate and dissolve it in 200 mL of deionized water to obtain a magnesium nitrate solution, add 3.5 mL (7 mol / L) of ammonia water to the magnesium nitrate solution, and let it stand for 1 hour to react to obtain a magnesium hydroxide slurry;

[0046] Step 2: Add 1.21 g (0.0225 mol) of ammonium chloride and 1.50 g (0.0048 mol) of dodecylethoxysulfobetaine to the magnesium hydroxide slurry, and stir to react for 2 h; dissolve 16.13 g (0.0540 mol) of sodium silicate in 150 mL of deionized water to obtain a sodium silicate solution, and use a circulation pump to add the sodium silicate solution drop by drop to the magnesium hydroxide slurry, and stir and ultrasonically disperse for 20 min;

[0047] Step 3: The slurry after ultrasonic treatment was transferred to a hydrothermal reactor, heated to 140 degrees by microwave, reacted for 2.5 hours, then heated to 220 degrees, continued to react for 10 hours, naturally cooled to room temperature, centrifuged and washed 4 times with deionized water, and the obtained filter cake was dried in an oven at 130 degrees for 18 hours, and ground through a 100 mesh sieve to obtain magnesium silicate powder;

[0048] Step 4: Take 6.00g (0.06mol) of magnesium silicate powder and add it to 100mL (6mol / L) of sodium hydroxide solution, stir and react at 140°C for 2.5h, cool to room temperature, centrifuge and wash four times with deionized water, dry the obtained filter cake in an oven at 60°C for 12h, and grind it through a 100-mesh sieve.

[0049] test:

[0050] The regeneration catalytic performance of the flower-spherical magnesium silicate anthraquinone degradation product regeneration catalyst prepared in Example 2 was tested, and the test steps were as follows: 5.00 g of the flower-spherical magnesium silicate anthraquinone degradation product regeneration catalyst prepared in Example 2 was added to 50 mL of working solution, and 50 μL of anthraquinone regeneration solution was taken at 72 h, placed in a 10 mL volumetric flask and fixed to volume with anhydrous methanol, and anthraquinone regeneration amount was tested on liquid chromatography. The flower-spherical magnesium silicate anthraquinone degradation product regeneration catalyst prepared in Example 2 has a high regeneration performance for anthraquinone degradation products, and the regeneration amount reaches 9.27 g / L within 72 h.

[0051] Example 3

[0052] A spherical magnesium silicate anthraquinone degradation product regeneration catalyst is prepared by the following method:

[0053] Step 1: Weigh 13.01 g (0.0560 mol) of magnesium nitrate and dissolve it in 200 mL of deionized water to obtain a magnesium nitrate solution, add 4 mL (6 mol / L) of ammonia water to the magnesium nitrate solution, and let it stand for 1 hour to react to obtain a magnesium hydroxide slurry;

[0054] Step 2: Add 1.51 g (0.0260 mol) of ammonium chloride and 1.51 g (0.0056 mol) of sodium lauryl polyether sulfate to the magnesium hydroxide slurry, and stir to react for 2 h; dissolve 17.02 g (0.0560 mol) of sodium silicate in 150 mL of deionized water to obtain a sodium silicate solution, and use a circulation pump to add the sodium silicate solution drop by drop to the magnesium hydroxide slurry, and stir and ultrasonically disperse for 20 min;

[0055] Step 3: The slurry after ultrasonic treatment was transferred to a hydrothermal reactor, heated to 150 degrees by microwave, reacted for 2 hours, then heated to 240 degrees, continued to react for 12 hours, naturally cooled to room temperature, centrifuged and washed 4 times with deionized water, and the obtained filter cake was dried in an oven at 140 degrees for 16 hours, and ground through a 100 mesh sieve to obtain magnesium silicate powder;

[0056] Step 4: Take 7.00g (0.07mol) of magnesium silicate powder and add it to 100mL (7mol / L) of sodium hydroxide solution, stir and react at 150°C for 2h, cool to room temperature, centrifuge and wash four times with deionized water, dry the obtained filter cake in an oven at 60°C for 12h, and grind it through a 100-mesh sieve.

[0057] test:

[0058] The regeneration catalytic performance of the flower-spherical magnesium silicate anthraquinone degradation product regeneration catalyst prepared in Example 3 was tested, and the test steps were as follows: 5.00g of the flower-spherical magnesium silicate anthraquinone degradation product regeneration catalyst prepared in Example 3 was added to 50mL of working solution, and 50μL of anthraquinone regeneration solution was taken at 72h, placed in a 10mL volumetric flask and fixed to volume with anhydrous methanol, and anthraquinone regeneration amount was tested on liquid chromatography. The flower-spherical magnesium silicate anthraquinone degradation product regeneration catalyst prepared in Example 3 has a high regeneration performance for anthraquinone degradation products, and the regeneration amount reaches 9.21g / L within 72h.

[0059] Comparative Example 1

[0060] The catalytic performance of a commercially available alumina-supported sodium hydroxide regeneration catalyst was tested, and the test steps were as follows: 5.00 g of a commercially available alumina-supported sodium hydroxide regeneration catalyst was added to 50 mL of working solution, 50 μL of anthraquinone regeneration solution was taken after 72 hours, placed in a 10 mL volumetric flask and made up to volume with anhydrous methanol, and the anthraquinone regeneration amount was tested on a liquid chromatography. The regeneration amount within 72 hours was 4.23 g / L, and the regeneration performance dropped to 2.36 g / L after 3 months of use.

Claims

1. A method for preparing a regeneration catalyst for anthraquinone degradation products of spherical magnesium silicate, characterized in that: The following steps are involved: Step 1: adding ammonia water to an aqueous solution of magnesium salt, and allowing to stand for reaction to obtain magnesium hydroxide slurry; Step 2: adding the ammonium salt and the growth inducer to the magnesium hydroxide slurry, stirring for reaction, then dropping the silicate solution into the magnesium hydroxide slurry, and performing ultrasonic treatment after the dropping is completed; Step 3: transferring the slurry after ultrasonic treatment to a hydrothermal reactor, heating with microwaves for reaction, cooling to room temperature after the reaction is complete, washing with deionized water by centrifugation, and drying the obtained filter cake to obtain magnesium silicate powder; Step 4: adding magnesium silicate powder to sodium hydroxide solution, stirring for reaction, washing and drying after the reaction is completed, and obtaining a spherical magnesium silicate anthraquinone degradation product regeneration catalyst.

2. The method for preparing the regeneration catalyst of the spherical magnesium silicate anthraquinone degradation product according to claim 1, characterized in that: In step 1, the magnesium salt is any one or more combinations of magnesium chloride, magnesium nitrate or magnesium sulfate.

3. The method for preparing the regeneration catalyst of the spherical magnesium silicate anthraquinone degradation product according to claim 1, characterized in that: In step 1, the concentration of the aqueous solution of the magnesium salt is 0.2-0.5 mol / L, the concentration of the ammonia water is 6-8 mol / L, and the molar ratio of Mg in the magnesium salt to the ammonia water is 1-2:

1.

4. The method for preparing the regeneration catalyst of the spherical magnesium silicate anthraquinone degradation product according to claim 1, characterized in that: The ammonium salt described in step 2 is any one or more combinations of ammonium chloride, ammonium nitrate or ammonium sulfate; the silicate is sodium silicate or potassium silicate.

5. The method for preparing the regeneration catalyst of the spherical magnesium silicate anthraquinone degradation product according to claim 1, characterized in that: The growth inducer described in step 2 is any one or more combinations of dodecyl ethoxy sulfobetaine, sodium laureth sulfate, and lauryl glucoside.

6. The method for preparing the regeneration catalyst of the spherical magnesium silicate anthraquinone degradation product according to claim 1, characterized in that: The concentration of the silicate in step 2 is 0.2-0.5 mol / L, the molar ratio of Si to Mg is 1-1.5:1, the molar ratio of ammonium salt to Mg is 1:2-1, and the molar ratio of growth inducer to Mg is 0.05-0.5:

1.

7. The method for preparing the regeneration catalyst of the spherical magnesium silicate anthraquinone degradation product according to claim 1, characterized in that: The procedure of microwave heating reaction in step 3 is to react at 120-150° C. for 2-4 h, then increase the temperature to 180-240° C. and continue the reaction for 6-12 h.

8. The method for preparing the regeneration catalyst of the spherical magnesium silicate anthraquinone degradation product according to claim 1, characterized in that: In step 4, the concentration of the sodium hydroxide solution is 5-10 mol / L; the stirring reaction temperature is 80-150° C., and the time is 2-4 h.

9. A spherical magnesium silicate anthraquinone degradation product regeneration catalyst, characterized in that: The catalyst is prepared by the method for preparing the regeneration catalyst of the degradation product of spherical magnesium silicate anthraquinone according to any one of claims 1 to 8.

10. The method for preparing the regeneration catalyst of anthraquinone degradation products of spherical magnesium silicate according to any one of claims 1 to 8 or the use of the regeneration catalyst of anthraquinone degradation products of spherical magnesium silicate according to claim 9 in the regeneration of anthraquinone degradation products.

Citation Information

Patent Citations

  • Preparation method of core-shell structured micro-nanosphere comprising magnetic core and magnesium silicate nano-sheet shell

    CN103071438A

  • Preparation method of attapulgite-based magnesium silicate anthraquinone regenerated catalyst, anthraquinone regenerated catalyst and application thereof

    CN117602636A

  • Process for the treatment of a silicate mineral

    US20150299823A1

  • Silicates with high ion exchange capacity derived from sepiolite and processes for their production

    US4542002A

  • Filler or a support for catalytically active substances, a process for producing said filler or support, a catalyst produced from said support, and the use of said catalyst

    WO1985003241A1